2005
DOI: 10.1128/mcb.25.4.1298-1308.2005
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40 Small t Antigen Mediates Conformation-Dependent Transfer of Protein Phosphatase 2A onto the Androgen Receptor

Abstract: The tumor antigens simian virus 40 small t antigen (ST) and polyomavirus small and medium T antigens mediate cell transformation in part by binding to the structural A subunit of protein phosphatase 2A (PP2A). The replacement of B subunits by tumor antigens inhibits PP2A activity and prolongs phosphorylationdependent signaling. Here we show that ST mediates PP2A A/C heterodimer transfer onto the ligand-activated androgen receptor (AR). Transfer by ST is strictly dependent on the agonist-activated conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 53 publications
8
78
0
Order By: Relevance
“…A recent study defined a PP2A-dependent role for polyoma small t in disrupting ARF-mediated activation of p53 (48). In addition, SV40 small t induces a conformational change in the PP2A A subunit that mediates PP2A binding to the androgen receptor (49). Although the interaction of small t with PP2A complexes is involved in regulating many signaling pathways, only some of those pathways are responsible for the transforming function of small t. Here we showed that the introduction of small t or suppression of PP2A B56g or Aa all lead to loss of AC-B56g complexes, constitutive phosphorylation of AKT, and cell transformation, suggesting a common mechanism for PP2A alterations and human cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study defined a PP2A-dependent role for polyoma small t in disrupting ARF-mediated activation of p53 (48). In addition, SV40 small t induces a conformational change in the PP2A A subunit that mediates PP2A binding to the androgen receptor (49). Although the interaction of small t with PP2A complexes is involved in regulating many signaling pathways, only some of those pathways are responsible for the transforming function of small t. Here we showed that the introduction of small t or suppression of PP2A B56g or Aa all lead to loss of AC-B56g complexes, constitutive phosphorylation of AKT, and cell transformation, suggesting a common mechanism for PP2A alterations and human cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it seems evident that direct binding of c-Jun to the C-terminal tail of DDX21 enhances the intrinsic RNA binding affinity of DDX21. Importantly, a similar "hit-and-run" mechanism resulting in conformational changes at the binding surface has been suggested recently to regulate protein-protein interactions (25,26).…”
Section: Discussionmentioning
confidence: 76%
“…Lipin, a target of insulin signaling, is dephosphorylated as a result of its interaction with MT (Schaffhausen et al, unpublished). The idea that MT might direct PP2A toward substrates is supported by the observations that SV40 ST increases the activity of PP2A for substrates such as histone H1 (339) and the androgen receptor (337). In a second scenario, MT might perturb the activity of PP2A complexes in cells, either in terms of inhibiting activity or by changing the range of B-subunit associations.…”
Section: Mt-associated Proteinsmentioning
confidence: 97%